THE EQUIVALENCE OF CULTURAL WORD TRANSLATION IN THE NOVEL CHILD OF ALL NATIONS BY MAX LANE - Yenna Artha Pitaloka; Muhammad Adam; Adi Prautomo (Prologue: Journal on Language and Literature, 2019)
This research explores the analysis of the type of translation procedures and the degree of meaning equivalence used in translating cultural words in the novel Semua Anak Bangsa by Pramoedya Ananta Toer into Child of All Nations by Max Lane. The objectives of this research are first, to find the types of translation procedures are used by a translator to translate cultural words in the novel Child of All Nations and second, to identify how cultural word translation to achieve the degree of meaning equivalence. The theory used is the translation procedures by Newmark and meaning equivalence by Bell. The methodology used is qualitative research in which the researcher presents the issues descriptively. As for data, they were collected from the cultural words in the dialogue and narration in the novel. After going through the analysis, the researcher concludes eleven translation procedures are used by the translator in this translation. There are transference, naturalization, cultural equivalent, functional equivalent, descriptive equivalent, through-translation, shifts or transpositions, synonymy, compensation, couplets, and notes-additions-glosses. The commonly procedure is cultural equivalent. The degrees of meaning equivalence are fully equivalent, partly equivalent, and different meaning. The commonly degree of meaning equivalence is fully equivalent.